Experiments on Possible Stone Age Glue Types - Werner Pfeifer (EXARC, 2015)
These experiments cover the making and testing of several possible glue types that might have been used in the hunter and gatherer period of the European Stone Age (without the aid of ceramics). Glue types produced in these experiments are: 1. Birch bark tar and pitch, 2. Pine wood tar and pitch, 3. Pine resin / wax glue, 4. Pine resin / wax / charcoal glue, 5. Hide glue and 6. Blue Bell glue